Primary Fallopian Tube Carcinoma: Results of a Single-Institutional Retrospective Analysis of 17 Patients with Evaluation of Staging and Prognostic Factors - Tounsi, Neserine; Bouazize, Hanen; Margheli, Ikram; Boujelbene, Nadia; Monia, Hechiche; Slimane, Maher; Rahel, Khaled (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: Primary carcinoma of the fallopian tubes is one of the less common gynecological cancers. It constitutes (0.14-0.18%) of gynecological malignancies. Our study aimed to review the managing process of primary carcinoma of the fallopian tubes in the mono-center institute and to identify prognostic factors impacting survival. STUDY DESIGN: A retrospective cohort study regarding patients with fallopian tube carcinoma treated between July 1991 and December 2005 was identified at the Tunisian anticancer institute “Salah Azaiez”. During this period, we have identified 17 patients. Data such as age, gravidity and parity, menopausal condition, symptoms reported by the patient on presentation, adjuvant therapy, stage of illness, surgical intervention, pathological findings, tumor recurrence, and previous surgical procedures were obtained from the patients’ reports. RESULTS: The average age at the time of diagnosis was 58 years. Fourteen of the included patients were postmenopausal. Surgery was the initial therapy for 15 patients. Optimal cytoreductive surgery was achievable in seven patients with no residual tumors. Histologic examination revealed that serous adenocarcinoma type was the predominant type. Two were in stage I and, four were in stage II; seven were in stage III and four in stage IV. The median follow-up time was 24 months. At the time of the final analysis, 11 patients died of disease. 5-year OS, DFS was 21% and 37% respectively. In our study, only the residual tumor was a significant prognostic factor predicting survival. CONCLUSION: Complete optimal surgery with no residual tumor was the main goal of the surgeon to improved survival in primary fallopian tube carcinoma.